2018
DOI: 10.2478/ejser-2018-0069
|View full text |Cite
|
Sign up to set email alerts
|

The Ins and Outs of Teamworking: When University Teachers, in-Service Secondary Teachers and Pre-Service Teachers Collaborate to Transform Learning

Abstract: Initiatives for teachers’ professional development should rely on the epistemology of practice, that is, be founded on the premise that reflective teachers construct professional knowledge and develop professional skills through practice and through planning, observing or analysing practice. Reflection about teaching action and reflection in teaching action triggers innovation, especially when teachers work together to create the necessary conditions to transform learning. This paper advocates in favour of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Because the evaluation method of examination does not directly promote the level of English thinking and logical argumentation of many learners, the range of applications will be limited. Masats and Guerrero [ 30 ] critically examined and found that the automatic evaluation system was not perfect either because some students were not proficient enough to effectively evaluate each other's articles in online mutual evaluation, and their attention was also focused on the language level as teachers' evaluation. Almanthari et al [ 31 ] found through the follow-up study of teacher teaching that the application of technology in mathematics teaching produced good teaching effects.…”
Section: Related Workmentioning
confidence: 99%
“…Because the evaluation method of examination does not directly promote the level of English thinking and logical argumentation of many learners, the range of applications will be limited. Masats and Guerrero [ 30 ] critically examined and found that the automatic evaluation system was not perfect either because some students were not proficient enough to effectively evaluate each other's articles in online mutual evaluation, and their attention was also focused on the language level as teachers' evaluation. Almanthari et al [ 31 ] found through the follow-up study of teacher teaching that the application of technology in mathematics teaching produced good teaching effects.…”
Section: Related Workmentioning
confidence: 99%
“…Working as a team leads to the emergence of better quality and efficient solutions (De Church & Mesmer-Magnus, 2010;Kwak, 2004). Masats and Guerrero (2018) also emphasize that both teachers and preservice teachers must have teamwork skills in order to facilitate their acquisition of professional knowledge. Therefore, it is very valuable to investigate the extent to which the preservice science teachers make sense of inquiry-based teaching pedagogy through individual and teamwork.…”
Section: Introductionmentioning
confidence: 99%
“…The steering group of the larger project is led by a university outreach office and is made up of head teachers and English teachers from the town's two secondary schools, members of the local council, the Catalan Education Department and university-based researchers -the latter group including the authors of this chapter. The project is aimed at boosting educational and professional outcomes generally, and English language competences in particular, of youth in the municipality (see Masats & Guerrero, 2018). Young people's educational outcomes in the town are among the poorest in Catalonia.…”
Section: Introducing the Site In Cataloniamentioning
confidence: 99%